Pulsed Magnetic Resonance to Signal‐Enhance Metabolites within Seconds by utilizing para‐Hydrogen. Issue 5 (8th May 2018) - Korchak, Sergey; Yang, Shengjun; Mamone, Salvatore; Glöggler, Stefan
Abstract: Diseases such as Alzheimer's and cancer have been linked to metabolic dysfunctions, and further understanding of metabolic pathways raises hope to develop cures for such diseases. To broaden the knowledge of metabolisms in vitro and in vivo, methods are desirable for direct probing of metabolic function. Here, we are introducing a pulsed nuclear magnetic resonance (NMR) approach to generate hyperpolarized metabolites within seconds, which act as metabolism probes. Hyperpolarization represents a magnetic resonance technique to enhance signals by over 10 000‐fold. We accomplished an efficient metabolite hyperpolarization by developing an isotopic labeling strategy for generating precursors containing a favorable nuclear spin system to add para ‐hydrogen and convert its two‐spin longitudinal order into enhanced metabolite signals. The transfer is performed by an invented NMR experiment and 20 000‐fold signal enhancements are achieved. Our technique provides a fast way of generating hyperpolarized metabolites by using para ‐hydrogen directly in a high magnetic field without the need for field cycling. Abstract : Quick and effective : A pulsed NMR experiment and isotope labeling strategy is introduced to signal‐enhance metabolites with para ‐hydrogen within only seconds.